y-5*-1=0

Simple and best practice solution for y-5*-1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-5*-1=0 equation:


Simplifying
y + -5 * -1 = 0

Multiply -5 * -1
y + 5 = 0

Reorder the terms:
5 + y = 0

Solving
5 + y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + y = 0 + -5

Combine like terms: 5 + -5 = 0
0 + y = 0 + -5
y = 0 + -5

Combine like terms: 0 + -5 = -5
y = -5

Simplifying
y = -5

See similar equations:

| 3x+5=2x+50 | | y-5*2=0 | | 252/288= | | x^2+3x-5=180 | | 2*0=-y+4 | | 2*-2=-y+4 | | 3*-1=-y+4 | | 3*0=-y+4 | | 3*-1=y+4 | | 3*0=-y+2 | | 3*1=-y+2 | | 3*-2=-y+2 | | 2*1=-y+3 | | 2*-2=-y+3 | | k(x)=log(x) | | 5x+40=2x | | y=-0.9*50+118 | | y=-0.9*40+118 | | 12x^4-28x^3-9x^2+28x+12=0 | | y=-0.9*30+118 | | y=-0.9*20+118 | | 4x-1=631 | | 4x+34-35=976 | | x(34+x)+(-35+2x)=631 | | 2*5+5y=80 | | x(34+x)=(-35+2x) | | 2*10+5y=80 | | x(34+x)=(-35+2xX) | | x(34+x)=(-35+2*x) | | 36=7x+8 | | 6x+4+x=3+5x+5 | | 3x-6=2x+11 |

Equations solver categories